2021
DOI: 10.2147/ijgm.s334972
|View full text |Cite
|
Sign up to set email alerts
|

Association Between HDL-C and Bone Mineral Density: An Cross-Sectional Analysis

Abstract: Background: Dyslipidemia has been found to contribute to increased risk of osteoporosis and its association with bone mineral density (BMD) remains controversial. We determined whether blood lipid levels are linked with change of BMD. Methods: In a large sample from the MIDUS II study, we sought to evaluate the relationship between blood lipid levels and BMD. Multivariate linear regression models and smooth curve analysis were constructed by controlling a great range of confounding factors. Results:The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…We found that increased tea consumption was positively associated with increased T-score which was mediated through the levels of subfractions of HDL (H.CH, H2CH, H2CE, H3FC, H3CH, and H3CE) and VLDL (V1CH, V1PL, V1FC, V1CE, V1LP, and V1TG) in our results. Meanwhile, HDL has been negatively correlated with BMD, and VLDL has been positively correlated with BMD according to previous research, which is an effective support for our results (10,72). A study has pointed out that long-term tea consumption is related to the reduction of HDL and may destroy the reverse cholesterol transport process mediated by HDL (73).…”
Section: Discussionsupporting
confidence: 87%
“…We found that increased tea consumption was positively associated with increased T-score which was mediated through the levels of subfractions of HDL (H.CH, H2CH, H2CE, H3FC, H3CH, and H3CE) and VLDL (V1CH, V1PL, V1FC, V1CE, V1LP, and V1TG) in our results. Meanwhile, HDL has been negatively correlated with BMD, and VLDL has been positively correlated with BMD according to previous research, which is an effective support for our results (10,72). A study has pointed out that long-term tea consumption is related to the reduction of HDL and may destroy the reverse cholesterol transport process mediated by HDL (73).…”
Section: Discussionsupporting
confidence: 87%
“…These three cholesterols indicated an inversive association with BMD in Chinese postmenopausal participants 12 . Peng Niu et al confirmed the inverse correlation of HDL-C level and BMD through their analysis of the MIDUS II study 21 . However, Irene Zolfaroli et al revealed that HDL-C level, but not TC and LDL-C, was positively relevant to the femoral neck and lumbar BMD 22 .…”
Section: Discussionmentioning
confidence: 88%
“…In most studies, a higher level of cholesterol was found to be associated with an increased risk of osteoporosis or a lower BMD ( 5 8 ). A non-association between cholesterol and BMD was also reported ( 9 11 ). Our findings that higher total cholesterol levels are associated with lower spine BMD do support the most previous research studies.…”
Section: Discussionmentioning
confidence: 93%